Pengaruh Kebijakan Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Daerah di Indonesia dalam Hubungan Pemerintah Pusat dan Daerah Terkait Keuangan Negara - Lusia Lestina Halawa; Mira Sukma; Evlin Limbong; Wahjoe Pangestoeti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the financial relationship between the central and regional governments within the framework of fiscal decentralization and its impact on regional economic growth. The main focus is to evaluate the contribution of the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) to Regional Original Revenue (PAD) and the equitable development between regions. Using a quantitative approach, the data was analyzed to assess how fiscal transfer policies support regional financial independence and sustainable development. The findings indicate that DAU and DAK significantly influence PAD growth; however, regional dependency on central government funds remains high. Furthermore, disparities in development between advanced and underdeveloped regions remain a significant challenge. This study recommends optimizing PAD management and implementing more equitable fiscal policies to support balanced development and inclusive economic growth in Indonesia.